First report of Melampsora epitea causing stem cankers on Salix pentandra in Alberta, Canada - Ramsfield, Tod D.; Feau, Nicolas; Tanguay, Philippe; Hamelin, Richard C.; Herath, Padmini; Bozic, Toso (Frontiers in Forests and Global Change, 2023)
In June, 2021, laurel willow (Salix pentandra) near Slave Lake, Alberta, was found to be infected by a Melampsora sp. that produced bright yellow urediniospores in uredia that were present on catkins, leaves, and stems. All Melampsora species previously reported in Canada are recorded as infecting leaves; therefore, further investigation was undertaken to ascertain the identity of this pathogen. To assess the relationship between this specimen and other Melampsora spp. previously collected from Canada, samples of willow leaves infected by Melampsora spp. were sourced from mycological herbariums located at the Laurentian Forestry Centre (QFB) and the Northern Forestry Centre (CFB, WINF(M)). DNA sequence data from the internal transcribed spacer (ITS) ribosomal RNA region of the fresh specimen, herbarium specimens, and DNA sequence data deposited within GenBank, were used to conduct a phylogenetic analysis. Sequencing and BLAST analysis of the material from the sample resulted in a 99.3% sequence identity match to Melampsora epitea “Mel J” collected from Larix laricina in New York State. The ITS sequence from the herbarium sample WINF(M)7356 (described as M. abieti-capraearum from Manitoba) had 100.0% identity with the Alberta sample. Additionally, specimens WINF(M)11892 (Melampsora sp. from Manitoba) and CFB8931 (Melampsora sp. from the Yukon) had 99.0% sequence identity with the Alberta sample. From these results we applied the identity of M. epitea to the rust discovered in Slave Lake, AB. With the current emphasis on willows for bioenergy production in Canada, growers must remain vigilant for this pathogen and the damages it could cause to willow plantations.